An Equal-Opportunity Approach to the Allocation of International Air - John Roemer; Humberto G. Llavador (University of California, Department of Economics, 1999)
How should international aid be distributed? The most common view is according to some utilitarian formula: in order to maximize the average growth rate of aid recipients or the growth rate of income of the class of recipient countries. Recently, the World Bank [7] has published a study demonstrating the importance of good economic management, within a recipient country, in transforming aid into economic growth. We identify good economic management with e ort, and ask, how should aid be distributed to equalize opportunities [among recipient countries] for achieving growth, according to Roemer''s [5] theory of equal opportunity. In addition, we calculate how aid should be distributed according to a utilitarian view. Both the equal-opportunity and utilitarian recommendations are less compensatory than actual aid policy (they would give less to many African countries than present policy does). We discuss the results.
Keywords: 330